Issues of improving the quality of education on the basis of analysis of variance - Kuchkarova D.F. Кучкарова Д.Ф.; Achilova D.A. Авилова Д.А. (Рroblems of engineering and professional education, 2023)
In the article, based on the analysis of the factors influencing the success of education, the problems of improving the quality of education in a higher educational institution are considered. To model the educational process in higher education institutions, knowledge about the interaction of various components of this process is required. Important components are the positive and negative factors characteristic of the participants in the learning process. One of the possible ways to analyze the interaction of factors is analysis of variance, which allows you to take into account the importance of the influence of each factor. The use of dispersion analysis allowed us to conclude that motivation is one of the most important positive factors affecting the success of training. The interaction of positive and negative factors at the same time leads to different results depending on the situation.